Adaptasi Budaya dan Akomodasi Komunikasi Peserta Inbound Pertukaran Mahasiswa Merdeka Angkatan 1 Universitas Muhammadiyah Makassar - Ningtias, Mista Aura; Lubis, Fardiah Oktariani; Susanto, Tri (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
The Merdeka Student Exchange Program is a component of the Merdeka Belajar Kampus Merdeka (MBKM) initiative that requires participants to engage in learning and interaction with students from various universities, representing diverse ethnicities, religions, races, and cultures. In the context of intercultural communication, cultural adaptation becomes a necessity for participants in the Merdeka Student Exchange Program. During the cultural adaptation process, inbound students from the Merdeka Student Exchange Program at Muhammadiyah University Makassar often experience culture shock, posing a challenge during the cultural adaptation process. To overcome culture shock, solutions can be found through the implementation of adaptation strategies, one of which is communication accommodation. The research method employed is a qualitative approach using descriptive methods. Data collection techniques involve interviews, observations, and document collection. In terms of data analysis, the study applies the theory proposed by Miles and Huberman, involving stages of data reduction, data presentation, and conclusion drawing. To ensure data validity, the research utilizes triangulation methods, both in terms of data sources and methodological approaches.